Investigating the State Regulation Mechanisms of Supply Chain Innovations in the Aspect of Developed Countries - Ildar M. Ablaev (International Journal of Supply Chain Management, 2018)
Abstract- The economic and technological development of the state in the contemporary world directly depends on supply chain innovations. Developed countries, such as Japan, invest 3% of gross domestic product (GDP) in financing innovation. The problem is that post-Soviet states such as Russia do not have a well functioning mechanism of state regulation of supply chain innovations. This situation leads to technological and economic lag. In this regard, the purpose of this article is to examine the mechanisms of the state regulation of supply chain innovations, using the example of developed and developing countries. For this purpose, a complex of complementary research methods was used, such as comparative analysis, systematization of data, as examples, the following states were considered: the USA, the UK, Germany and China. As a result, key features of state policy of considered states are pointed out, such as tax deductions, reducing bureaucracy, building up public-private enterprises. Also, the main tasks, solutions, which directly affect the development of the innovation sector, are highlighted.